POLA RUANG KAWASAN PERDESAAN KECAMATAN KATINGAN TENGAH KABUPATEN KATINGAN - Amiany (Jurusan Arsitektur UPR, 2018)
In determining the direction of development and the use of space in an area, a spatial plan is needed which becomes a joint reference for the Regional Government and the community. The urgency of the existence of a spatial plan is increasing because as a district that has recently been established, Katingan District is actively implementing development. Without careful planning, development will occur sporadically, irregularly and may even cause problems in the future.Katingan Tengah District is a sub-district located in the Central part of the district with the capital of Tumbang Samba District. Land use in Central Katingan Subdistrict is dominated by open land and forests, where some of them are Plantation, agriculture and also a region with hilly contours. This makes the Katingan Tengah sub-district has great potential for the development of plantation products and agricultural products. Other potentials are providing enormous opportunities for the development of the region itself. This potential is the availability of vast vacant land supported by a fairly strategic location in the Katingan Regency spatial plan and Central Kalimantan Province.The need for the construction of a region that can accommodate the needs of regional development on the one hand and maintain the existence of forest areas on the other hand is the background for the compilation of a Spatial Plan for Rural Areas in Central Katingan District. The use of regional development concepts that are environmentally sound such as revitalizing existing riverbank housing areas or developing integrated service centers that can increase the yields of plantations and agriculture in Rural Areas in Central Katingan District.